Preserving Patchogue: A Small Institution Rehouses and Digitizes Glass Plate Negatives. Issue 2 (June 2018) - Menzo, Daniel J.
In 2015, the Greater Patchogue Historical Society in Long Island, New York, received a gift of nearly 2, 000 glass plate negatives dating from the early 20th century. While the donor alluded to rare images of this small town and its people, the collection presented a series of preservation concerns. Many of the objects were soiled, and almost all were still in their original acidic paper sleeves. Determined to both protect and utilize the collection, this small institution, with the assistance of a graduate student intern, formalized a preservation plan that also created multiple points of access to the visual and historical information that these objects contained. After minimally cleaning, rehousing, and photographing a selected portion of the negatives, the digital files were later processed with editing software so that the organization's members and local citizens could see the historic images. In addition to digitizing the negatives, the original sleeves were imaged to preserve valuable information, such as people's names, the location of views, or a negative's date. This ongoing project is an example of how smaller institutions can make a meaningful influence in their local communities by preserving photographic objects and implementing methods of digitization.